Biochemical Indicators of Fruits of Melon Varieties Suitable for Storage in the Conditions of the Republic of Karakalpakstan - Davletbayevich, Sultanov Jetkerbay (Journal of Medical Genetics and Clinical Biology, 2024)
This article presents information on the biochemical parameters of the fruits of melon varieties grown in the climate conditions of the Republic of Karakalpakstan.